Independent effects of sham laparotomy and anesthesia on hepatic microRNA expression in rats. - Werner, Wiebke.; Sallmon, Hannes.; Leder, Annekatrin.; Lippert, Steffen.; Reutzel-Selke, Anja.; Morgül, Mehmet Haluk.; Jonas, Sven.; Dame, Christof.; Neuhaus, Peter.; Iacomini, John.; Tullius, Stefan G.; Sauer, Igor M.; Raschzok, Nathanael. (2016)
Background: Studies on liver regeneration following partial hepatectomy (PH) have identified several microRNAs (miRNAs) that show a regulated expression pattern. These studies involve major surgery to access the liver, which is known to have intrinsic effects on hepatic gene expression and may also affect miRNA screening results. We performed two-third PH or sham laparotomy (SL) in Wistar rats to investigate the effect of both procedures on miRNA expression in liver tissue and corresponding plasma samples by microarray and qRT-PCR analyses. As control groups, non-treated rats and rats undergoing anesthesia only were used.; Keywords: Hepatectomy, Liver regeneration, microRNA, Sham laparotomy, Surgical stress.; Springer Open.